Manejo de residuos sólidos municipales del distrito de Calzada, provincia de Moyobamba – San Martin - Cervantes Chuquihuanga, Roiser (2012)
This research work is a study with the sole purpose to contribute to the solution of some social problems of collective interest, as is the case of improper handling of municipal solid waste which are experiencing our peoples from the homeland, in addition we want to put at the disposal of the authorities and civil population a systematizing of basic information in what concerns the suitable managing of the solid residues of municipal area; by specifying some technical considerations and guidelines to provide an adequate public cleaning services in the Calzada town, n this sense the information contained in this document can be validated as reference basis for the formulation of plans, programs, and Environmental Sanitation projects mainly, the same that must be implemented according to the order of priority, since we are talking about and putting at risk the health and quality of life of the population. In this report it is possible to find valuable information regarding the production per capita of Solid Residues for inhabitant / day, likewise we have to our scope information of physical characterization of the solid domestic residues, and finally requirements and technical information are had to the scope for an offer of Sanitary Manual Landfill of the Calzada city. Under this scenario, the present work entitled "municipal solid waste management district of Calzada, Moyobamba province - San Martin", is the result of an investigation and determination of the physical characteristics of the solid waste generated in the city Calzada. It includes the topics of generation per-capita, density, physical composition and dampness of the solid residues from different sources. The research is complemented by a survey of the habits and attitudes of the users of the existing municipal system. On the base of this information one presents a series of conclusions, several recommendations are formulated. With the present investigation, it has allowed us to come to the conclusion of that the ppc of the Calzada locality is 0.60 Kg/ Hab/day, the average density is of 108.92 Kg/m and 81.99 % dampness , on what it is recommended to meet beginning to the development of an integral plan of environmental management of the solid residues, which contemplates the design of the routes of compilation, education and environmental education, closing of the existing dump and location of a place adapted to arrange the solid residues (a sanitary landfill)